Analisis Keragaman Genetik Galur Kedelai Transgenik Toleran Cekaman Aluminium dan Varietas Non-Trasngenik Berdasarkan Marka SSR - Pardal, Saptowo J.; Rahayu, V. R.; Nugroho, K.; Suharsono, Suharsono (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
High genetic diversities are important factors in the development of new crop varieties. In vitro technique and Genetic Engineering are applicable for development of crop variability that is not found in the gene pool. Genetic variation may be derived from genetic variations in cells or in chromosomes. Variations in the cells may be obtained from cell mutations or polysomic mutations of a certain cells during the in vitro culture (plant regeneration in vitro). Genetic variations in chromosome may be caused by gene insertion, changes of chromosom structures (crossings), as well as changes of genes and cytoplasms. Changes of genetic characters may be improved by inserting novel gene into the cells target. To improve the plant tolerances to abiotic factors, tolerance gene constructs can be inserted to the target cells. For example, by inserting the Aluminum tolerance gene construct such as MaMt2 gene its can induce genetic diversity in transgenic soybean lines resulted from transformation. Research results showed that genetic diversity in transgenic soybean lines was found based on microsatellite marker (SSR= Simple Sequence Repeat). The genetic diversity produced by using genetic manipulation can provide chances to develop new plant genotipes that contain Al tolerance character.